JSS3: MATHEMATICS - 1ST TERM
-
Binary Number System I | Week 15 Topics|1 Quiz
-
Binary Number System II | Week 26 Topics|1 Quiz
-
Word Problems I | Week 34 Topics|1 Quiz
-
Word Problems with Fractions II | Week 41 Topic|1 Quiz
-
Factorization I | Week 54 Topics|1 Quiz
-
Factorization II | Week 63 Topics|1 Quiz
-
Factorization III | Week 73 Topics|1 Quiz
-
Substitution & Change of Subject of Formulae | Week 82 Topics|1 Quiz
-
Simple Equations Involving Fractions | Week 93 Topics|1 Quiz
-
Word Problems | Week 101 Topic|1 Quiz
Completing the Square
Topic Content:
- Completing the Square
To make a quadratic expression a perfect square, add half the coefficient of x (or whatever letters are used) and square the result.
Worked Example 7.3.1:
Solve the following:
i. x2 + 5x
ii. y2 + 9y
iii. h2 – 3h
iv. x2 + 7x
v. x2 – 10x
vi. \( \scriptsize y^2 \: – \: \normalsize \frac{2y}{3} \)
Solution
i. x2 + 5x
Step 1: half the coefficient of x
⇒ \( \frac{5}{2} \)
Step 2: square the result
⇒ \(\scriptsize x^2 + \normalsize {\left(\frac{5}{2}\right)}^2 \\ = \left ( \scriptsize x + \normalsize \frac{5}{2} \right)^2 \)
⇒ \({\left(\frac{5}{2}\right)}^2 = \frac{25}{4}\)
⇒ \( \frac{25}{4} \) must be added to make it a perfect square
ii. y2 + 9y
= \(\scriptsize y^2 + \normalsize {\left(\frac{9}{2}\right)}^2 \\ = \left ( \scriptsize y + \normalsize \frac{9}{2} \right)^2 \)
⇒ \( \frac{81}{4} \) must be added to make it a perfect square
iii. h2 – 3h
= \(\scriptsize h^2 \: – \: \normalsize {\left(\frac{3}{2}\right)}^2 \\ = \left ( \scriptsize h \: – \: \normalsize \frac{3}{2} \right)^2 \)
⇒ \( \frac{9}{4} \) must be added to make it a perfect square
iv. x2 + 7x
= \(\scriptsize x^2 + \normalsize {\left(\frac{7}{2}\right)}^2 \\ = \left ( \scriptsize x + \normalsize \frac{7}{2} \right)^2 \)
⇒ \( \frac{49}{4} \) must be added to make it a perfect square
v. x2 – 10x
= \(\scriptsize x^2 + \normalsize {\left(\frac{10}{2}\right)}^2 \\ = \left ( \scriptsize x + \normalsize \frac{10}{2} \right)^2 \)
⇒ \( \frac{100}{4} \: \scriptsize = 25 \) must be added to make it a perfect square
vi. \( \scriptsize y^2 \: – \: \normalsize \frac{2y}{3} \)
= \( \scriptsize y^2 \: – \: \left (\normalsize \frac{\frac{2y}{3}}{2} \right)^2 \)
= \( \scriptsize y^2 \: – \: \left (\normalsize \frac{2}{3} \: \times \: \frac{1}{2} \right)^2 \)
= \(\scriptsize y^2 \: – \: \normalsize {\left(\frac{2}{6}\right)}^2 \\ = \scriptsize y^2 \: – \: \normalsize {\left(\frac{1}{3}\right)}^2 \\ \left (\scriptsize y \: – \: \normalsize \frac{1}{3}\right)^2 \)
⇒ \( \frac{1}{9} \) must be added to make it a perfect square